The Queen of Attolia : a queen's thief novel - Turner, Megan Whalen (Greenwillow Books, 2017)
Forsaken by the gods and left to his own devices, Eugenides, Royal Thief of Eddis, summons all his wit and wiles in an attempt to conquer the rival Queen of Attolia.